Analyzing Business Feasibility at Gas Station For PT. Total Oil Indonesia - Yazid, Muhammad; Sumirat, Erman (The Indonesian Journal of Business Administration, 2012)
The government replan conversing BBM to BBG program as one of other solutions to decrease subsidy gradually. PT. Total Oil Indonesia as one of oil and gas companies in Indonesia sees the problem as an opportunity to build SPBG to support the government’s program. To analyze business feasibility, business situation analysis was done by using Feasibility Study and Sensitivity Analysis. The primary indicator used to determine the feasibility was NPV (Net Present Value), IRR (Internal Rate of Return) and PBP (Payback Period). The result of analysis of information gathered showed that SPBG development project would be optimal and feasible to be started if BBM subsidy was removed, so that the gas price would be 40% cheaper than premium price, the availability of equal gas-buying price as raw material, and also the implementation of government’s plan to give free converter kit to the society. To get it well implemented TOI will take a part in cooperating with the government program to develop step in constructing gas station with 4 scenarios already explored before that is firstly applied to the public transportation and then to all of Indonesian people. The steps are installing the Hybrid Station to see how the market works and then going to the next step is to construct pipeline station system and further more (for stable condition) the last step is to build a Mother – Daughter Station package. The implementation done in a working program will be held for short-term (5 years) as pilot project evaluation and long-term (15 years). Keywords: BBM Subsidy, Conversion from BBM into BBG, Feasibility Analysis, Gas Refueling Station (SPBG)